Rapid Behavioral Recovery Based on Environmental Enrichment of a White-Throated Toucan (Ramphastos Tucanus: Ramphastidae) Affected by Collision Trauma - Vergara-Egert, P; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier Inc., 2022)
Captive animals that have experienced traumatic events require a high range of care prior to reintroducing them into their natural habitat; and this care should ensure their welfare in captivity. This report shows the ethological evolution of beneficial effects attributed to environmental enrichment. Specifically, the report focuses on the recovery of a white-throated toucan (Ramphastos tucanus: Ramphastidae) affected by a collision trauma resulting in a skull fracture, which received treatment and care in the Taricaya wildlife rescue center (Madre Selva, Peru). An environmental enrichment protocol was implemented for 30 days, recording all activities during this period. We performed generalized linear models to identify significant trends in the observed activities. We showed that inactive time and self-mutilation significantly decreased, while walking, eating, and washing activities increased during the study period. Temporal improvement in toucan welfare may be associated with higher energy (walking), better nutrition (eating), and decreased stress, as shown by reduced self-mutilation. Our report provides evidence on the favorable outcome of environmental enrichment in a toucan, raising its importance as a management tool for veterinary practitioners in wildlife rescue centers. © 2022 Elsevier Inc.
Keywords: Ethology; Animal welfare; Rescue centers; Ex situ conservation